Path Dependence and Innovation: A Dichotomy in Internationalization - Scherrer, Suzana Maria; de Vasconcellos, Silvio Luís (Revista de Negócios, 2019)
This study attempts to understand the role played by path dependence in the evolution of the international business of firms faced with circumstances in which innovation becomes a challenge. Decisions, both related to innovation and to internationalization, are interdependent and are related to prior events, generating repetitive effects and triggering self-reinforcing processes that affect future decisions. We employed descriptive, qualitative research methods, in the form of a single case study, conducting interviews at a large footwear firm and with independent industry experts, then analyzed these data using content analysis. The results enabled us to map the events internal and external to the organization that led to the decisions taken and which, at certain points, were reactions to innovation and to acceleration or deceleration of the internationalization process, providing evidence of path dependence. This study has implications for management practice, since it deals with the combined effects on decision making of path dependence at the levels of the organization and of the industry. At the level of the industry, it makes contributions related to the interconnections between decisions taken within an organization, which in turn affect the future decisions of other firms in the same industry. Factors limiting our results include the facts that just one firm was studied and that the historical data are also dependent on the limitations of human rationality and may not, therefore, include certain elements of perception linked to the period of time during which the facts narrated took place.